2018
DOI: 10.2147/copd.s151939
|View full text |Cite
|
Sign up to set email alerts
|

Do not do in COPD: consensus statement on overuse

Abstract: BackgroundTo identify practices that do not add value, cause harm, or subject patients with chronic obstructive pulmonary disease (COPD) to a level of risk that outweighs possible benefits (overuse).MethodsA qualitative approach was applied. First, a multidisciplinary group of healthcare professionals used the Metaplan technique to draft and rank a list of overused procedures as well as self-care practices in patients with stable and exacerbated COPD. Second, in successive consensus-building rounds, descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Therefore, adherence to the guidelines should be preferred to provide proper care, even when physicians encounter more severely ill patients. In accordance with previous studies, we found overtreatment was more frequent in patients with underlying chronic pulmonary disease and a suspected mild to moderate community-acquired pneumonia [25,26]. Thus, for these patients with pulmonary disease, physicians should be extra alert to potential overtreatment.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, adherence to the guidelines should be preferred to provide proper care, even when physicians encounter more severely ill patients. In accordance with previous studies, we found overtreatment was more frequent in patients with underlying chronic pulmonary disease and a suspected mild to moderate community-acquired pneumonia [25,26]. Thus, for these patients with pulmonary disease, physicians should be extra alert to potential overtreatment.…”
Section: Discussionsupporting
confidence: 91%
“…We used the focus group [ 17 , 18 ] technique with the patients, because of its inclusive approach which encourages various topics through which the participants can explain their own experiences and respond to what other participants say. In the case of the HCP, we selected a nominal group technique [ 19 ], together with an interactive voting system, which allowed us to hierarchically structure the ideas put forward by the participants.…”
Section: Methodsmentioning
confidence: 99%
“…40 Therefore, the treatment can be maintained for several hours with less risk of skin breakdown, 41 which avoids alveolar de-recruitment and oxygen reduction, which typically occur during NIV interruption. Moreover, HFNC can reduce inspiratory effort 42 similar to NIV, without the downsizes and concerns of air leakage, patient-ventilator synchrony, and the need of sedation, 43 which offers a good balance between adequate oxygenation and comfort. 44 However, unlike NIV, HFNC cannot deliver high PEEP levels.…”
Section: Advantages and Disadvantages Compared With Standard Oxygenmentioning
confidence: 99%